Vermifiltration Ecological Treatment for the Re‐Use of Food Waste Digestate. (1st November 2013) - Lin, Hui; Diemont, Stewart A. W.; Toland, Timothy; Tao, Wendong; Daley, Douglas; Johnson, David L.
ABSTRACT: : A vermifiltration ecological treatment system (VETS) was developed to treat bio‐digested food waste and create nitrate‐rich fertilizer. Conventional processes to treat digester effluent are typically not designed for value‐added products from the treatment process. This research is the first documented example of an ecological treatment system (ETS) used for digester waste. Experiments were conducted at three different inflow rates. Removal efficiency of ammonium nitrogen (NH4 + ‐N), carbonaceous biochemical oxygen (CBOD5 ), and total suspended solids (TSS) were consistently larger than 90%; NOx − ‐N displayed large increases in the system. With increased flow rates, NH4 + ‐N, NOx − ‐N and orthophosphate phosphorus (ortho‐PO4 3− ‐P) concentration in the effluent also increased, but TSS and CBOD5 concentrations in the effluent did not change. Used as the first unit process in the system, vermifiltration showed high efficiency in NH4 + ‐N and CBOD5 reduction. Design formulas were developed using literature in combination with this study to facilitate design of ETSs.